English for specific purposes and the communication skills in adults, during the year 2020 - Rodríguez González, Estefany Nicole (2021)
Nowadays English is a global language. The majority of adults need to learn English for different reasons. When they finish the school and achieve a basic level of English. Sometimes adults begin the university and study a career like law, medicine, police and others. Some adults have a job or want a better job opportunity where need to speak English according to the environment that they are involve. This Adults English learners for academic or work purposes have specific needs. For this reason, is necessary a teaching program applying English for specific purposes to develop communication skills. This research work is directed to determine the importance of English for specific purposes in the communicative skills in adults during the year 2020. It was observed in a group of adults that are security guards who work at an important security company located in the north of Guayaquil city in Ecuador where students show important difficulties to communicate in English language. They were not able to produce short dialogues due to lack of vocabulary acquisition, answer some questions, transmit messages or were not likely to be motivated to speak in the English language. The security guards will want a real, practical and purposeful English language training courses. For this reason, this research project proposes a guide for a teaching program applying English for specific purposes to help students improve their communication skills..........